1999
DOI: 10.1017/s0252921100048788
|View full text |Cite
|
Sign up to set email alerts
|

Radial-Velocity Standard Stars

Abstract: Abstract. We review the history of the IAU Radial Velocity Standard Stars and give a status report on recent efforts at the HarvardSmithsonian Center for Astrophysics to establish an absolute velocity zero point for these stars and to improve their usefulness for intercomparing the results from different instruments and observatories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
2
27
1
Order By: Relevance
“…We reduced the spectra following standard practice for this instrument 56 . We cross-correlated the spectra with an archival observation of Barnard's Star and found that the absolute radial velocity of G 229-20 A/B is 17.9 ± 0.1 km s −1 (on the IAU standard system 57 ). We also inspected the Hα line for G 229-20 A/B from the FIES spectrum.…”
Section: Spectroscopy Of G 229-20 A/bmentioning
confidence: 99%
“…We reduced the spectra following standard practice for this instrument 56 . We cross-correlated the spectra with an archival observation of Barnard's Star and found that the absolute radial velocity of G 229-20 A/B is 17.9 ± 0.1 km s −1 (on the IAU standard system 57 ). We also inspected the Hα line for G 229-20 A/B from the FIES spectrum.…”
Section: Spectroscopy Of G 229-20 A/bmentioning
confidence: 99%
“…The spectral coverage was 3820-4500 Å at a mean resolution of R ∼4500. Copper-Argon lamps were used between each exposure to calibrate the spectra to an RMS of 0.03 Å (2 km s −1 at 4500 Å), and the typical resolution was 1.0 Å FWHM at 3900 Å and 0.82 Å FWHM at 4400 Å. Spectra were Doppler corrected to the heliocentric frame and checked against the radial velocity standards HD131156 (G8V), HD146233(G2V), HD161096(K2III), HD161797(G5IV), and HD171391(G8III) from Stefanik et al (1999) before comparison to previous datasets.…”
Section: Observationsmentioning
confidence: 99%
“…The modern era of radial velocity standards occurred with the work by the Geneva group led by Michel Mayor and Stephane Udry, the University of Victoria group led by Collin Scarfe and Robert McClure, and the group at the Harvard-Smithsonian Center for Astrophysics led by David Latham and Robert Stefanik (Mayor & Maurice 1985;Scarfe et al 1990;Latham et al 1991Latham et al , 2002. An excellent summary of the history of radial velocity standards through 1999 is provided by Stefanik et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Three excellent radial velocity programs provided standards with high accuracy and integrity (Stefanik et al 1999;Udry et al 1999a,b), all of them constituting a modern velocity zero-point with accuracy better than 0.3 km s −1 . Additional excellent stellar radial velocity measurements were made by Nordström et al (2004); Famaey et al (2005) at accuracies of ∼0.3 km s −1 , and also by the Fick Observatory at Iowa State University, and at the Mt.…”
Section: Introductionmentioning
confidence: 99%